2021
DOI: 10.3390/separations8060086
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid HPLC Method for the Concurrent Determination of Several Antihypertensive Drugs from Binary and Ternary Formulations

Abstract: A rapid, synchronized liquid chromatographic method was established for the estimation of hydrochlorothiazide (HCZ), amlodipine (AMD), olmesartan (OLM), telmisartan (TEL), and irbesartan (IRB) in binary and ternary coformulations using the same chromatographic conditions. Five analytes were separated on a Zorbax C18 column using isocratic elution with a mobile phase consisting of acetonitrile, methanol, and 20 mM phosphate buffer (pH 3.5) in a ratio of 45:20:35% v/v. The analytes were detected at a wavelength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For quality control, a suitable analytical approach for assaying these anti-diabetic medicines is necessary. All laboratories are interested in developing easy, rapid, and reliable analytical processes for analyzing pharmaceuticals in various formulations, which can be accomplished by estimating a larger number of medications using a single approach employing the same stationary and mobile phases [21]. For the measurement of remogliflozin alone and in combination with other antidiabetic medications, only a few analytical procedures have been established.…”
Section: Introductionmentioning
confidence: 99%
“…For quality control, a suitable analytical approach for assaying these anti-diabetic medicines is necessary. All laboratories are interested in developing easy, rapid, and reliable analytical processes for analyzing pharmaceuticals in various formulations, which can be accomplished by estimating a larger number of medications using a single approach employing the same stationary and mobile phases [21]. For the measurement of remogliflozin alone and in combination with other antidiabetic medications, only a few analytical procedures have been established.…”
Section: Introductionmentioning
confidence: 99%
“…Pareto charts evident that the factors of organic phase composition, flow rate, and buffer pH have a profound influence on response factors, peak area, retention time, and tailing factor (Figure 3A–C). The ‘t’ value of the factors was between t value limit and Bonferroni limit, which indicate the significant influence of the factors [33]. From the screening study, it was found flow rate, the organic phase composition, and buffer pH had a significant ( p < 0.05) influence on CAAs, hence they were chosen as CMP for the optimization study.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage assay obtained was in the range of 98% to 102% for all the analytes. The method offered good linearity in the concentration of 2-30 μg/mL for Hydrochlorothiazide, 1-15 μg/mL for Amlodipine, 5-160 μg/mL for Olmesartan and Telmisartan and 10-300 μg/mL for Irbesartan [44] .…”
Section: Issn: 2320-4850 [90] Coden (Usa): Ajprhsmentioning
confidence: 93%